Analysis of Conservation and Environmental Education Strategies in the Nirwana Beach Tourism Area, Padang City - Amri, M; Aisyah, Siti; Rustam, Dicky; Munzir, Abdullah (Grouper, 2025)
Nirwana Beach is one of the leading coastal tourism destinations in Padang City, offering significant potential for development as an educational and sustainable tourism area. However, the management of this area still faces various challenges, such as low community participation, limited environmental education facilities, and the lack of integration of conservation programs into tourism activities. This study aims to analyze conservation and environmental education strategies at Nirwana Beach to support sustainable coastal area management. The study was conducted using a quantitative approach using questionnaires with 100 respondents, supported by field observations and interviews with key informants. Data were analyzed descriptively and then followed by a SWOT analysis approach. The results showed that tourist awareness and concern for the environment were high (score >4.0), but educational facilities and community involvement were still limited. The SWOT analysis resulted in a total score of strengths (1.30), weaknesses (0.35), opportunities (1.22), and threats (0.52), placing conservation and education strategies in Quadrant I (aggressive strategies). The main recommended strategies include developing educational programs based on direct experience, providing environmental information facilities, involving local communities, and promoting the area as an environmentally friendly tourism destination. With its dominant potential strengths and opportunities, this area needs to be managed through multi-stakeholder synergy to create a tourist destination that is not only economically attractive, but also contributes to environmental conservation and public education